(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
The relationship between empathy and literature is understudied in the English language arts context. English language arts (ELA) educators wonder if reading can produce skills beyond those of comprehension and other ELA skills within students. Although empathy can be difficult to measure, some in the English language arts education community have begun to investigate whether they can cultivate empathy, perspective-taking, and open-mindedness within their students. Through research of some studies and articles surrounding this topic, it appears that empathy can be cultivated within students through literature when paired with discussion, writing, and reflection, and that cultivating empathy within students is integral to developing critical thinking, informed, and open-minded individuals.